Steam pop during cavo-tricuspid isthmus ablation shown by intracardiac echocardiography - Santoro, Amato (J Cardiol Cases, 2020)
Steam pop (SP) refers to audible sound related to the intramyocardial explosion when tissue temperatures reach 100 °C. In this case the SP was recorded using intracardiac echocardiography (ICE), using Sound-star probe and Smart-touch catheter with ablation index (AI) module (Biosense-Webster Inc., Diamond-Bar, CA, USA). Guided by the anatomical reconstruction (EAM) and electrograms, we applied radiofrequencies (RF) in a “point-by-point” along the entire line on cavo-tricuspid-isthmus (CTI) using a target of an AI ≥500. The tip-tissue force recorded was 12–18 g and a power of 35 W. ICE imaging was important so that the anatomical position of the catheter tip can be precisely monitored. During RF, ICE showed a growing, hyperechogenic intramyocardial bubble at the catheter-tissue interface. ICE imaging showed a hyperechogenic intramyocardial formation at the moment of occurrence of the SP. ICE imaging showed that the formation suddenly expanded to a sphere over the course of several seconds. After SP we reduced the RF output energy from 35 W to 30 W. After RF line on CTI the patient had no complications and no recurrence of atrial flutter was recorded. <Learning objective: The use of intracardiac echocardiography during cavo-tricuspid-isthmus ablation permits the detection of the increase of microbubbles before steam pop formation.>